A multiple case study of selected home based-tutorial centers - Tan, Klayre Angela M.
ABSTRACT The study aimed to examine the dynamics of merging the workspace and the dwelling space in the case of home-based tutorial centers. It employed a multiple case study approach and data gathering methods such as observation, interview and photo documentation. A purposive sampling design was applied in selecting the five (5) tutorial centers that were studied. The interview respondents were the owners of the tutorial centers. Data gathering instruments include an interview questionnaire printed on a short bond paper, pen, notepad, iPhone and a Nikon D3000 SLR. Findings revealed that although tutorial work dominated the home spatially and temporally, the respondents were able to manage both home and tutorial obligations well because they had household helpers. The main considerations of the respondents in locating the tutorial areas were the size of the available space and its distance from the private areas of the home. Respondents who did not have extra space in their homes transformed their living and dining areas into tutorial areas. In general, there were concerns with privacy, crowding and territoriality mainly because of the limited space allotted for the workspace and dwelling space and the number of people who had to utilize these areas. The displacement of some domestic spaces in favor of the workspace means that many of the domestic and personal activities had to be given up. The respondents resorted to strategies in order to cope with these concerns but overall, the workspace was not successfully integrated within the home. The study concludes that merging the workspace and the dwelling space will be effective only if there is an extra room or space in the home that can accommodate the workspace.